Comparison of metabolite profiles and policosanol contents in the sprout of Oriental wheat cultivars (Triticum turgidum ssp. turanicum) - Choi, Euna; Park, Jisu; Hong, Min-Jeong; Jin, Chang Hyun; Kim, Bo-Ram; Nam, Bomi; Na, MinKyun; Kil, Yun-Seo; Han, Ah-Reum (Frontiers in Nutrition, 2025)
BackgroundOriental wheat (Khorasan wheat; Triticum turgidum ssp. turanicum; Poaceae) is a tetraploid wheat species that has gained recognition as a superfood due to its high fiber content and nutrient density. Despite its nutritional benefits, limited information is available regarding the metabolite profiles of its sprouts, particularly across different cultivars.MethodsIn this study, metabolite profiles of sprouts from four Oriental wheat cultivars, obtained from the Rural Development Administration’s Genebank, were investigated. An ultra-high performance liquid chromatography–time-of-flight mass spectrometry (UHPLC–QTOF MS) method was employed to analyze and annotate the compounds present. Principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) were utilized to explore the metabolite differences among the cultivars. Additionally, feature-based molecular networking analysis was conducted to support metabolite identification and contribute to marker discovery. Gas chromatography–mass spectrometry (GC–MS) was used to quantify policosanols in the samples.ResultsFourteen compounds were annotated, with eight being detected in T. turgidum ssp. turanicum for the first time. PCA score plots and loading plots revealed distinct metabolite differences among the cultivars based on their country or region of collection. OPLS-DA score plots and S-plots indicated the differential expression of five flavonoid C-glycosides in samples from Afghanistan and five nitrogen-containing compounds characteristic of samples from Türkiye. The total policosanol content ranged from 356.3 to 400.1 mg/100 g, marking the first quantification of policosanols in Oriental wheat using GC–MS.ConclusionThese findings provide valuable insights into the phytochemical metabolism of Oriental wheat sprouts and illustrate the influence of geographical conditions on metabolite profiles. The study highlights the potential of Oriental wheat sprouts as a valuable dietary source of policosanols.